Answer:x=3
Step-by-step explanation:
D( x )
x+2 = 0
x = 0
x+2 = 0
x+2 = 0
x+2 = 0 // - 2
x = -2
x = 0
x = 0
x in (-oo:-2) U (-2:0) U (0:+oo)
(9*x-7)/(x+2)+15/x = 9 // - 9
(9*x-7)/(x+2)+15/x-9 = 0
(x*(9*x-7))/(x*(x+2))+(15*(x+2))/(x*(x+2))+(-9*x*(x+2))/(x*(x+2)) = 0
x*(9*x-7)+15*(x+2)-9*x*(x+2) = 0
9*x^2-9*x^2+8*x-18*x+30 = 0
30-10*x = 0
(30-10*x)/(x*(x+2)) = 0
(30-10*x)/(x*(x+2)) = 0 // * x*(x+2)
30-10*x = 0
30-10*x = 0 // - 30
-10*x = -30 // : -10
x = -30/(-10)
x = 3
x = 3
Answer:
82°
Step-by-step explanation:
The acute angles in a right triangle are complementary. The other one is ...
90° -8° = 82°
Image ?....?.?.?..?.?..?.?.?.?..?.?...?.?.?.?..??...?.?.??..?.?.? Smh simpsimpjdjs
Answer:
6 and 11
Step-by-step explanation:
n1 = n + 5
ns^2 = 3 + 3nb
6^2 = 3 + 3(11)
36 = 3 + 33
11 = 6 + 5
Answer:
60°
Step-by-step explanation:
ABCO is a parallelogram (opposite sides are parallel).
AO is equal to the radius of the circle, so BC must also equal the radius.
CO is equal to the radius of the circle, so AB must also equal the radius.
If we draw a line from O to B, we split the parallelogram into two triangles. Since OB is equal to the radius of the circle, each triangle is an equilateral triangle. Therefore, angle A is 60°.